Effect of grape juice press fractioning on polysaccharide and oligosaccharide compositions of Pinot meunier and Chardonnay Champagne base wines. (1st October 2017) - Jégou, Sandrine; Hoang, Duc An; Salmon, Thomas; Williams, Pascale; Oluwa, Solomen; Vrigneau, Céline; Doco, Thierry; Marchal, Richard
Highlights: Press fractioning of Pinot meunier and Chardonnay grape juices were performed. Polysaccharide and oligosaccharide base wine content was affected by press fractioning. Total polysaccharide concentration of wines decreases throughout the pressing cycle. Abstract: Press fractioning is an important step in the production of sparkling base wines to segregate the grape juices with different qualities. Grape juice fractions were collected during the pressing cycle at industrial and laboratory scales. The Pinot meunier and Chardonnay Champagne base wines obtained from the free-run juice and the squeezed juices exhibited strong differences from the beginning to the last step of pressing cycle for numerous enological parameters. Significant changes in polysaccharide (PS) and oligosaccharide (OS) base wine composition and concentration were found as the pressing cycle progressed. During the pressing cycle, the total PS concentration decreased by 31% (from 244 to 167 mg/L) and 32% (from 201 to 136 mg/L) in the Pinot meunier and Chardonnay wines respectively. The wine OS amounts varied between 97 and 139 mg/L. The polysaccharide rich in arabinose and galactose (39–54%) and mannoproteins (38–55%) were the major PS in the base wines.